pengaruh pemberian dosis pupuk kandang kambing dan dosis pupuk NPK terhadap pertumbuhan dan hasil tanaman jagung manis (Zea mays saccharata Sturt): pemberian dosis pupuk kandang kambing dan dosis pupuk NPK terhadap pertumbuhan dan hasil tanaman jagung manis (Zea mays saccharata Sturt) - Rizki Ardianto Nugroho; Priyono Priyono; Kharis Triyono (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2022)
This study on the Effect of Dosage of Organic Goat Manure and Dosage of NPK Fertilizer on Growth and Yield of Sweet Corn (Zea Mays Saccharata Sturt) was conducted on 7 May – 23 July 2021, in the experimental garden of the Faculty of Agriculture, Slamet Riyadi University, Surakarta. The altitude of the place is ± 105 meters above sea level with alluvial soil type. This study aims to examine the effect of dose of goat manure and dose of NPK fertilizer on growth and yield of sweet corn. A completely randomized design (CRD) was utilized in this investigation, which was set up in a factorial fashion. The treatment consisted of two components, each of which was repeated three times. (1) Goat manure (K) with four levels: control (K0), dose 0 gr/polybag (K1), dose 250 gr/polybag (K2), dose 500 gr/polybag (K3), and a dose of 750 gr/polybag (2). Control (M0), dose of 0 gr/polybag (M1), dose of 6.075 gr/polybag (M2), dose of 12.15 gr/polybag (M3) dose of 18,225 gr/polybag were the four levels of NPK fertilizer application. The procedure was done three times for a total of 48 combinations. The data is analyzed using the F test and analysis of variance. Meanwhile, the BNJ test was employed at a 5% level to establish the significance of the differences between treatments. Plant height, number of leaves, weight of cobs with cobs, weight of cobs without husks, weight of wet pods, weight of dry pods, number of cobs, weight of dry shells, and weight of 100 seeds were among the parameters measured. The findings revealed that (1) goat manure had no effect on any of the observations. (2) Plant height, weight of dry stover, weight of wet stover, weight of cobs with cabbage, weight of cobs without cabbage, weight of dry shells, and weight of 100 seeds were all significantly affected by NPK fertilizer. (3) There was no significant interaction between goat manure (K) and NPK fertilizer (M) on any of the parameters. Keywords : NPK fertilizer, goat manure, sweet corn